Comparative study of internalized and externalized symptoms of Caraquenian children as a function of food insecurity at home - Bassi, Liliana (2022)
This research aimed to compare the internalizing (anxiety and depression) and externalizing (hyperactivity) symptoms of Caraquenian children based on the level of food insecurity reported by their parents. A simple retrospective design was proposed with a sample of 200 children, aged between eight and twelve, and their representatives, in charge of reporting the food insecurity levels in their homes and the symptoms of perceived hyperactivity in their children. For the analysis of results, the non-parametric Mann-Whitney´s U technique was used to compare anxiety, depressive and hyperactive symptoms based on high and low levels of food insecurity. Results suggest moderate conditions of food insecurity in the households. Furthermore, regarding the set of internalizing symptoms evaluated, it was found that households with greater food insecurity tend to have children with greater manifestations of nervousness (U = 865.50, p < .001, r = .36), physiological symptoms (U = 1123.00, p = .02, r = .22) and cognitive and interpersonal reactions to depression (U = 1080, p = .01, r = .25). Similar results were obtained for the externalizing symptoms of hyperactivity (U = 961.50, p = .001, r = .31). Psychological implications of the differences are discussed.